Analysis of Corrosion Rate in Centrifugal Pump Intake Pipes (Case Study: PDAM Bengkalis Indonesia) - Sabri Sabri; Syahrizal Syahrizal (University of Muhammadiyah Jakarta, 2020)
Pipe is one of the important components for a clean water treatment system that is used to transport water flow. For the process of producing water from the reservoir to the tank, it still uses galvanized steel pipes, this type of pipe is used by PDAM Bengkalis. Based on the previous explanation, it is very necessary to do a research on the corrosion rate in the intake pipe to determine the level of corrosion that occurs by using the Ultrasonic Thickness Gauge test by looking at the thickness reduction in the pipe. This study uses an experimental method. Corrosion is a process of decreasing the quality of metal materials caused by chemical reactions between metal materials and other elements in their environment. From this study, 2 types of galvanized steel pipes are found with different ages, they are 7 years old pipe with 6 inches lenght and 10 years old pipe with 10 inches length, while the corrosion rate that occurred in the intake pipe in zone A was 0.245 mm/year, 0.392 mm/year, and 0.248 mm/year, for zone B is 0.335 mm/year and 0.268 mm/year, in zone C is a straight line pipe as a comparison factor with a corrosion rate of 0.473 mm/year, 0.470 mm/year, 0.287 mm/year, 0.464 mm/year, and 0.306 mm/year.